2015
DOI: 10.1158/1541-7786.mcr-14-0118
|View full text |Cite
|
Sign up to set email alerts
|

Annexin 2–CXCL12 Interactions Regulate Metastatic Cell Targeting and Growth in the Bone Marrow

Abstract: A nnexin 2 (ANXA2) plays a critical role in hematopoietic stem cell (HSC) localization to the marrow niche. In part, ANXA2 supports HSCs by serving as an anchor for stromal-derived factor-1 (CXCL12/SDF-1). Recently it was demonstrated that prostate cancer (PCa) cells, like HSCs, use ANXA2 to establish metastases in marrow. The present study determined the capacity of ANXA2 expression by bone marrow stromal cells (BMSC) to facilitate tumor recruitment and growth through ANXA2-CXCL12 interactions. Significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 47 publications
4
32
0
Order By: Relevance
“…However, NE stimulation of a similar coculture between PCa cells and GAS6 −/− OBs led to no significant change in proliferation, indicating that GAS6 regulation by adrenergic signaling can lead to reactivation of DTCs. These results agree with previous reports demonstrating that GAS6 can activate tumor cell dormancy both in vitro and ex vivo (6,10,23,32). While GAS6 has been established to regulate immune homeostasis (46), its role within the complex signaling environment of the healthy HSC niche is currently unknown.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, NE stimulation of a similar coculture between PCa cells and GAS6 −/− OBs led to no significant change in proliferation, indicating that GAS6 regulation by adrenergic signaling can lead to reactivation of DTCs. These results agree with previous reports demonstrating that GAS6 can activate tumor cell dormancy both in vitro and ex vivo (6,10,23,32). While GAS6 has been established to regulate immune homeostasis (46), its role within the complex signaling environment of the healthy HSC niche is currently unknown.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, we and others have demonstrated that PCa cells metastasize to the HSC niche and interact with osteoblasts. To determine the extent to which NE alters niche-localization signals expressed by osteoblasts, we examined mRNA expression by PCR for the following adhesion molecules: Annexin II ( ANXA2 /Annexin IIR ( ANXA2R )), Notch/Jagged, and homing molecule CXCL12 (5,6,32). As shown in Figure 4A, NE treatment of OBs decreased mRNA expression of Anxa2 but failed to induce significant changes in the expression of Jagged 1 , Anxa2R or CXCL12 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may indeed be the first in vivo evidence to support several examples that linked AnxA2/p11 with ion channels (Gerke and Moss, 2002;Gerke et al, 2005;Avenali et al, 2014). Finally, inoculation of prostate cancer cells mixed with bone marrow stromal cells from the AnxA2 KO mice revealed that AnxA2 binding to stromal-derived factor 1 is crucial for recruitment, growth and survival of prostate cancer cells in the bone marrow microenvironment (Jung et al, 2015).…”
Section: Anxa2 Ko Micesupporting
confidence: 55%
“…Other researchers argue that the tumour stroma is primarily derived from precursor cells present within the local primary tumour, while bone marrow-derived circulating precursor cells are rare 161 . In a metastatic setting, MSCs and osteoblasts attract tumour cells to the bone marrow by secreting a local gradient of chemoattractants, such as SDF1 or GAS6 143,162164 . Once in the bone marrow, breast cancer cells can sequester SDF1 and affect the response of haematopoietic cells to this signalling factor in in vitro co-culture assays 165 .…”
Section: Stroma–cancer Interactionsmentioning
confidence: 99%